The Influence of Smartboard Digital Media on Student Learning Outcomes in Zakat Fiqh Subjects at MTsN 1 Pasuruan - Habil Syahril Haj; M. Mujab; Rahmat Aziz (PALAPA, 2025)
The low learning outcomes of students, caused by the limited variety of learning methods and media, are a problem that needs to be overcome in the world of education. This study aims to: (1) analyze the influence of the use of Smart Board digital media on improving student learning outcomes in fiqh zakat materials; and (2) comparing learning outcomes between the experimental class and the control class. The research method used is a quantitative approach with a quasi-experimental design of a non-equivalent control group type. Data collection instruments include measurement of cognitive, affective, and psychomotor aspects through pretest and posttest. The results of the analysis showed that the use of Smart Boards significantly improved student learning outcomes. In the cognitive aspect, the average score increased from 49.17 to 76.90 (p < 0.001); in affective aspects from 49.59 to 73.66 (p < 0.001); and on the psychomotor aspect from 49.56 to 73.79 (p < 0.001). Multivariate Variance Analysis (MANOVA) showed significant differences between the experimental and control groups (Wilks' Lambda = 0.524, F(3, 56) = 16.928, p < 0.001) with a Partial Squared Eta value of 0.476. Based on these findings, it was concluded that the use of Smart Board media contributed to an increase in student learning outcomes by 47.6%. The implications of this study show the importance of integrating interactive digital media in improving learning effectiveness.